IMPLEMENTASI KURIKULUM PAI PADA MATA PELAJARAN AKIDAH AKHLAK DALAM SISTEM FULL DAY SCHOOL - Solekhah Nur Afifah; Joko Subando (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
This article aims to explore the implementation of the Islamic Religious Education (PAI) curriculum, especially in the subject of Aqidah Akhlak in the full day school system. This system offers challenges and opportunities in shaping the character of students. Through a descriptive qualitative approach, this article analyzes how the PAI curriculum is implemented, the teaching methods used, and its impact on strengthening the values ​​of aqidah and morals of students. The results of the study indicate that the full day school system allows for deeper value-based learning, although it requires innovative strategies to maintain a balance between academic needs and spiritual strengthening of students.